AB1222-HPR Hypervigilance to Emotional Subliminal Images in Patients with Fibromyalgia. (9th June 2015) - Peláez, I.; Mercado, F.; Barjola, P.; Cardoso, S.
Abstract : Background: Fibromyalgia (FM) is a chronic condition characterized by the presence of pain, fatigue and cognitive dysfunction, among other symptoms. Previous research (Duschek et al., 2014) also indicated that patients show an hypervigilance pattern to pain and negative information that interferes with the processing of other events by capturing attention resources and generating cognitive difficulties. This hypervigilance seems to be dependent of automatic processes. Duschek and collaborators (2013) show the first evidence of cognitive disruption associated with processes non-dependent from conscious and controlled resources by an implicit memory task. An index that reflects these hypervigilance processes may be the N2 which has been associated with an unpleasant stimulus (Olofsson et al., 2008), for that is one of the most frequently component show a sensitive to attentional capture by emotional distractor (Carretié, 2014). Objectives: Explore by ERP the hypothesis of generalized hypervigilance in FM using mask emotional images that have to processes non-dependent from conscious controlled resources. Methods: 46 women participated in this study (23 FM patients and 23 healthy controls). They participated in a passive visual task, where the emotional images (neutral, negative and pain-related) are masked to prevent their conscious perception. Each trial start whit a mask (450ms), then the emotional picture presented (26ms) followed by other mask (450ms). ERP were recorded at sixty scalp electrodes. On the basis of the topographical distribution of grand-averaged ERP activity and previous studies, peak amplitude values were computed for 150-250 ms (N2). The Signal Detection Theory was used to analyze the image detection. Results: ANOVAs indicated that amplitudes of N2 at parieto-occipital regions were different between groups (p<0.05). Specifically, FM patients as compared to control group showed more negativity amplitude for the 3 emotions. However, there were not found an interaction effect between types of emotion by group. Conclusions: Present results indicate that ERPs associated with conscious processing of emotional stimuli (N2 component) are also elicited by subliminal images where people report to be unaware of it. Also it is suggested that fibromyalgia patients have a generalized hypervigilance response even to images that could not be processed consciously. This effect could play an important role in the augmented pain perception for these patients. These data provide objective evidence that some sub-processes of attention could be altered in FM. Further research, however, is needed to fully understand and delimitate this possible alteration. References: Carretié, L. (2014). Exogenous (automatic) attention to emotional stimuli: a review. Cognitive, Affective, & Behavioral Neuroscience, 1-31. Duschek, S., Werner, N.S., Winkelmann, A. Wankner, S. (2013). Implicit Memory Function in Fibromyalgia Syndrome. Behavioral Medicine 39 (1), 11-16. Duschek, S., Werner, N, Limbert, N., Winkelmann, MD. & Montoya, P. (2014). Attentional bias toward negative information in patients with fibromyalgia syndrome. Pain medicine, 15: 603-612. Olofsson, J., Nordin, S., Sequeira, H. & Polich, J. (2008). Affective picture processing: an integrative review of ERP findings. Biol Psychol, 77 (3): 247-265. Acknowledgements: Supported by grant PI13/01759 from the Ministry of Economy and Competitiveness: Institute of Health Carlos III (ISCIII) of Spain. Disclosure of Interest: None declared